Investigation on the combined effect of aging temperatures and cooling medium on rheological properties of asphalt binder based on DSR and BBR. (30th April 2019) - Wang, Di; Falchetto, Augusto Cannone; Riccardi, Chiara; Poulikakos, Lily; Hofko, Bernhard; Porot, Laurent; Wistuba, Michael P.; Baaj, Hassan; Mikhailenko, Peter; Moon, Ki Hoon
Abstract : In this paper, the combined effect of aging temperatures and cooling medium on the rheological properties of asphalt binder was experimentally investigated and evaluated. Two 70/100 penetration grade binders, which were part of the core materials used by the active RILEM committee CMB-252, were selected for this purpose. The materials were artificially aged to six different conditions, first with the Rolling Thin Film Oven Test (RTFOT) at three different temperatures (123°C, 143°C, and 163°C), and then, with the standard Pressure Aging Vessel (PAV). Next, temperature and frequency sweep (T-f-sweep) tests were performed on the entire set of materials by using the Dynamic Shear Rheometer (DSR) from −30°C to 80°C while low-temperature creep tests were conducted on the long-term aged asphalt binders with the Bending Beam Rheometer (BBR) devices in air and in ethanol, respectively. Then, the 2 Spring 2 Parabolic element 1 Dashpot model (2S2P1D) and Huet model were used to evaluate the rheological properties of asphalt binders based on the DSR and BBR results, respectively. Moreover, two parameters, crossover temperature, Tδ=45°, and the difference in critical temperature, Δ Tc, were used to evaluate the aging properties of the materials. Finally, the relationship between the time domain complex modulus based on DSR and the creep stiffness obtained with the BBR was established to investigate the effect of the cooling medium at low-temperatures. The results indicate that a temperature reduced process may lead to a mitigation of the short-term aging of asphalt binders, while a temperature reduction of only 40°C can result in a consistently milder long-term aging. In the BBR test, higher creep stiffness and smaller m -values can be observed in the air compared to ethanol. Huet and 2S2P1D models show that complex modulus and creep stiffness share the same core parameters only in the case of air. Based on the finding in this research, the temperature reduced mixing process and the use of air for BBR creep tests are recommended.